2012
DOI: 10.1111/j.1741-4369.2012.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Faith, phonics and identity: reading in faith complementary schools

Abstract: Thousands of UK school children spend considerable time during a lengthy period of their youth learning to read, or decode, a 'religious classical', the liturgical language connected to their faith. Drawing on recent theories of reading, identity and literacy practices, this paper briefly describes and seeks to share tentative thoughts about some common issues around the teaching and learning of religious classicals within minority ethnic faith settings. It presents a comparative textual analysis of a central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The few available studies on the topic pointed out that in the first decades after the migration to Europe (1960s and1970s), mosque pedagogy has been largely modelled by practices in the countries of origin, namely a pedagogical approach emphasising teacher dominance, authoritarian teaching style, harsh discipline and rote learning (Cherti and Bradley 2011;Pels 2014). Memorisation persisted as an inherent part of mosque pedagogy as learning how to pronounce Qur'anic verses and recite correctly is an important aim (Gent 2011;Rosowsky 2013). Some studies report changes in mosque education and even talk of 'major transformations' as pedagogical practices are translated and re-contextualised in European societies over the decades (Che Noh et al 2014;Pels 2014).…”
mentioning
confidence: 99%
“…The few available studies on the topic pointed out that in the first decades after the migration to Europe (1960s and1970s), mosque pedagogy has been largely modelled by practices in the countries of origin, namely a pedagogical approach emphasising teacher dominance, authoritarian teaching style, harsh discipline and rote learning (Cherti and Bradley 2011;Pels 2014). Memorisation persisted as an inherent part of mosque pedagogy as learning how to pronounce Qur'anic verses and recite correctly is an important aim (Gent 2011;Rosowsky 2013). Some studies report changes in mosque education and even talk of 'major transformations' as pedagogical practices are translated and re-contextualised in European societies over the decades (Che Noh et al 2014;Pels 2014).…”
mentioning
confidence: 99%
“…In the context of quranic app practices in focus in this article, it is therefore important to note that when Roshina, Zohal, Homa and Guled talk about 'Arabic', they do not refer to any variety of Arabic, but typically to the highly specialized, strictly codified and emotionally laden variety of Classical Arabic. This engagement is elaborately described in Rosowsky's (2008Rosowsky's ( , 2010Rosowsky's ( , 2012Rosowsky's ( , 2013Rosowsky's ( , 2015 extensive sociolinguistic and ethnographic research in faith literacies in the UK. Rosowsky has focused primarily on Muslim faith communities and on quranic schools, but has also explored Jewish cheder and Sikh gurdwara faith complementary schools, and his research for instance covers the nature of reading instruction and questions of language choice in the faith complementary schools (Rosowsky, 2013), young Muslim's script choices (Rosowsky, 2010) and the performative nature of religious literacy practices (Rosowsky, 2012).…”
Section: )mentioning
confidence: 99%
“…Rosowsky has focused primarily on Muslim faith communities and on quranic schools, but has also explored Jewish cheder and Sikh gurdwara faith complementary schools, and his research for instance covers the nature of reading instruction and questions of language choice in the faith complementary schools (Rosowsky, 2013), young Muslim's script choices (Rosowsky, 2010) and the performative nature of religious literacy practices (Rosowsky, 2012). Building on Fishman (1989), Rosowsky conceptualizes the liturgical language which children and young people learn to read, memorise and recite within faith complementary schools as a 'religious classical' (Rosowsky 2012(Rosowsky , 2013, and h is research highlights the important symbolic meaning of the religious classical for individual and collective identity formation. As we will see in the analysis, the symbolic value of Classical Arabic also features prominently in Roshina, Zohal, Homa and Guled's quranic app practices.…”
Section: )mentioning
confidence: 99%
“…On the other side of the spectrum, studies conducted by critical scholars have drawn attention to contradictions between mosque education and schools. Rosowsky (2013) who conducted research in three mosques in the UK, observed that students were taught to decode the sacred script ignoring the meaning of the words they read. He suggests that this type of instruction may have serious implications for reading in schools, 'to the extent where meaning of the words becomes incidental, and where such nonunderstanding is also not disconcerting to the young reader' (p. 76).…”
Section: Scholarly Debates On Mosque Educationmentioning
confidence: 99%